2016
DOI: 10.1194/jlr.m067942
|View full text |Cite
|
Sign up to set email alerts
|

Use of lipidomics to investigate sebum dysfunction in juvenile acne

Abstract: inflammatory responses (1-3). Quantitative and qualitative modifications of sebaceous lipids likely trigger inflammatory responses causative of acne lesions commonly called comedones (4-7). Juvenile acne, which affects approximately 80% of adolescents in industrialized countries, develops during puberty when androgens and other endocrine factors stimulate sebum secretion, thereby generating conditions for development of lesions (8). Studies aimed at the identification of lipid alterations involved in acne path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 36 publications
8
73
0
Order By: Relevance
“…However, the relative average diglyceride content in patients with IA was significantly lower than that in patients without IA. Prior research has shown that triglyceride levels are closely related to the occurrence of acne . Our results are consistent with this work and indicate that triglyceride levels may be associated with the occurrence of IA.…”
supporting
confidence: 92%
“…However, the relative average diglyceride content in patients with IA was significantly lower than that in patients without IA. Prior research has shown that triglyceride levels are closely related to the occurrence of acne . Our results are consistent with this work and indicate that triglyceride levels may be associated with the occurrence of IA.…”
supporting
confidence: 92%
“…There are several techniques available for acne examination, comprising new photographic techniques and biometric analysis of sebum . Histopathology represents an optimal method for microscopic morphology lesion evaluation, but is limited due to its invasiveness, cosmetic consequences, and inability to apply to lesion follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…While lesion‐associated SGs are atrophic, sebum production in acne is abnormally high, and the composition of acne sebum is distinct from that in healthy skin . Moreover, certain sebaceous lipids have comedogenic properties.…”
mentioning
confidence: 99%